ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SD ISLAM AL-AKBAR MOJOKERTO - Khoir, Ismi (Jurnal Ilmiah Ibtida, 2024)
The Merdeka Curriculum gives educators the flexibility to design quality learning, in accordance with the needs and context of the student's learning environment. The implementation of the Merdeka Curriculum began to be implemented at Al-Akbar Islamic Elementary School, Mojokerto in the 2022/2023 academic year. This research aims to describe and analyze the implementation of Merdeka Curriculum in Indonesian language learning in class IV of Al-Akbar Islamic Elementary School. This research method uses a qualitative approach to data collected through observation techniques, interviews, and documentation. The results of this study indicate that the implementation of the Merdeka Curriculum in Indonesian language learning in class IV of Al-Akbar Islamic Elementary School has been implemented well, in accordance with the concept of the Merdeka Curriculum. However, there are also supporting and inhibiting factors in the implementation process. One of the supporting factors is the workshop related to the Merdeka Curriculum held by the school and for the inhibiting factor is the limited time in making class administration.